Towards markerless motion capture: Model estimation, pose initialization and tracking - Sundaresan, A. (2007)
Motion Capture (Mocap) is the process of analysing and expressing human motion in mathematical terms. Components of a markerless motion capture system: - Segmentation in Laplacian Eigenspace - Model and Pose Estimation - Pose tracking